Heating of Nanosized Liquid Water in High-Intensity Terahertz Pulses - 黄自谦 杨荣瑶 蒋维洲 章其林 (Chinese physics letters, 2016)
Non-equilibrium molecular dynamics simulations of liquid water in picosecond high-power terahertz pulses are performed by using a non-polarizable potential model. Numerical results show that the energy absorption of water molecules exhibits a pronounced resonance with THz pulses in the frequency range of 14-17 THz. With the THz pulse at resonant frequencies, the maximum temperature is about 562 K by heating the water at room temperature. Further investigation indicates that the results are independent of the size of the nanoscale water box. The efficiency of energy transfer by resonant absorption is more than seven times of microwave heating. These studies show promising applications of ultrashort THz pulses.